Mental Health Awareness Programme curbs stress problems - Siti Nur Azwin, Zulkapri (2021)
KUANTAN, 15 October 2021 - In conjunction with the Universiti Malaysia Pahang (UMP) 2021 Counselling Month Celebration, Employee Assistance Programme (EAP) in collaboration with the Counselling and Psychology Division, Department of Student Affairs (JHEP) recently organised the Suicide Prevention Programme: No Way Out.